2022
DOI: 10.1039/d1lc01113h
|View full text |Cite
|
Sign up to set email alerts
|

On the acoustically induced fluid flow in particle separation systems employing standing surface acoustic waves – Part I

Abstract: Experimental and numerical studies on the acoustically induced fluid flow at the center of pseudo-standing surface acoustic waves, as typically employed in Lab-on-a-Chip devices for particle separation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 98 publications
(174 reference statements)
2
19
0
Order By: Relevance
“…The displacement amplitude is an important parameter for this work, which only influences the energy of SAW in the investigated power range. The estimation of with the supplied electrical power is based on the following relationship [ 35 ]. where is the aperture of the IDTs and is a material dependent factor.…”
Section: Experimental Set-up Materials and Methodsmentioning
confidence: 99%
“…The displacement amplitude is an important parameter for this work, which only influences the energy of SAW in the investigated power range. The estimation of with the supplied electrical power is based on the following relationship [ 35 ]. where is the aperture of the IDTs and is a material dependent factor.…”
Section: Experimental Set-up Materials and Methodsmentioning
confidence: 99%
“…As the volume flow rate was controlled in the experiment a smaller cross-section results in larger velocities. To quantitatively assess the agreement in the patterns a correlation between the experimental and simulated velocity fields was performed (for more details see Sachs et al 36 ). This analysis gives correlation coefficients 37 of ≥95% for the data of Fig.…”
Section: Discussionmentioning
confidence: 99%
“…A detailed description on the fabrication of the microchannel using polydimethylsiloxane (PDMS) can be found in Part I. 34…”
Section: Methodsmentioning
confidence: 99%
“…Although this provides a useful guidance for the design of basic setups, a critical particle size cannot be used universally, as demonstrated in Part I of this work. 34 Furthermore, Devendran et al (2016) 35 and Fakhfouri et al (2018) 36 showed that there is an additional spatial dependence of the relative dominance between the two forces.…”
Section: Introductionmentioning
confidence: 99%